Gifted and talented children 4-11 : understanding and supporting their development - Macintyre, Christine, 1938- 4 0 16; 5 (London : Routledge, 2008)
A guide to understanding and supporting the development of gifted and talented children, ages four to eleven, covering parents' views, a biological perspective, an environmental perspective, and asynchronous development, and including practical activities.
Includes bibliographical references and index.
Adult.
Keywords: 2 -- 0; 6; Education;Education. -- Gifted children;Gifted children -- Great Britain.;Great Britain; 20; 2